Dampak Media Sosial Tiktok terhadap Kemampuan Kognitif Anak Usia 5-6 Tahun - Siti Mariam; Rachmah, Huriah; Dedih Surana (Bandung Conference Series: Early Childhood Teacher Education, 2025)
Abstract. This study aims to identify the impact of tiktok social media on cognitive abilities of children aged 5-6 years. Given the increasing use of social media among children, especially tiktok. This research is very relevant to understand how these applications affect children's cognitive development. This research uses a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation from three informants who are parents of children who use TikTok. The research location took place in three different places in the cities of Bandung and Cimahi. The results showed that the use of TikTok can have positive and negative impacts on children's cognitive abilities, depending on the content accessed and the time spent using the application. This study provides recommendations for parents to be more careful in giving children access to social media, as well as the importance of supervision and guidance in its use to support children's cognitive abilities optimally. Abstrak. Penelitian ini bertujuan untuk mengidentifikasi dampak media sosial tiktok terhadap kemampuan kognitif anak usia 5-6 tahun. Mengingat meningkatnya penggunaan media sosial dikalangan anak-anak, terutama tiktok. Penelitian ini sangat relevan untuk memahami bagaimana aplikasi tersebut mempengaruhi perkembangan kognitif anak. Penelitian ini menggunkan pendekatan kualitatif dengan metode studi kasus. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi dari tiga informan yang meruapakan orangtua anak-anak yang menggunakan tiktok. Lokasi penelitian berlangsung di tiga tempat berbeda di kota Bandung dan Cimahi. Hasil penelitian menunjukkan bahwa penggunaan tiktok dapat memberikan dampak positif dan negatif terhadap kemampuan kognitif anak, tergantung pada konten yang diakses dan waktu yang dihabiskan dalam menggunakan aplikasi tersebut. Penelitian ini memberikan rekomendasi bagi orangtua untuk lebih berhati-hati dalam memberikan akses kepada anak terhadap media sosial, serta pentingnya pengawasan dan bimbingan dalam penggunaannya umtuk mendukung kemampuan kognitif anak secara optimal.